Respostas
respondido por:
13
Boa noite!
Resolvendo a equação temos:
-x-2x-4=11
-3x-4=11
-3×=11+4
-3×=15 . (-1)
3x= -15
x= -15/3
x= -5
Qualquer dúvida, deixe-a nos comentários.
Bons estudos!
Resolvendo a equação temos:
-x-2x-4=11
-3x-4=11
-3×=11+4
-3×=15 . (-1)
3x= -15
x= -15/3
x= -5
Qualquer dúvida, deixe-a nos comentários.
Bons estudos!
respondido por:
13
-x-2x-4 = 11
-3x = 11+4
-3x = 15
3x = -15
x = -5
R = -5
espero ter ajudado
:)
-3x = 11+4
-3x = 15
3x = -15
x = -5
R = -5
espero ter ajudado
:)
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás